Study protocol: Return to Country, an Australia-wide prospective observational study about returning First Nations renal patients home - Alan Cass; Mandy Truong; Scott Jones; Stephen McDonald; Sandawana William Majoni; Yomei Jones; Cecilia Preece; Fiona Heerink; Andrew John Mallett; Cherian Sajiv; Khalil Patankar; Eddie Mulholland; et al. (BMJ Open)
Introduction In Australia, kidney failure treatment disparities exist between Aboriginal and/or Torres Strait Islander (First Nations) and non-First Nations people. Despite persistent calls from First Nations patients with kidney failure, they are less likely to have treatment that allows them to live at home.Methods and analysis This is a prospective, multicentre study based in Australia. The aim of the study is to characterise the socioeconomic, environmental, health service and biomedical factors driving the health outcomes and patterns of health service utilisation experienced by First Nations patients and investigate whether health service changes to address these identified barriers can achieve higher rates of renal replacement therapy at home on country. This will be achieved by mixed-methods data collection at health service (audit and process data), staff (surveys and qualitative interviews) and patient (survey testing, feedback sessions, health outcomes) levels. A process evaluation will identify barriers and enablers to health services changes in relation to cultural safety. Baseline and follow-up data will be compared to assess the extent to which health services change their service delivery and the impact on health outcomes for First Nations patients with kidney failure. Qualitative and quantitative data will be integrated to provide an in-depth understanding of project outcomes and impacts.Ethics and dissemination This study is funded by the National Health and Medical Research Council of Australia (GNT1158075). Ethics approval has been obtained so far from the Human Research Ethics Committee (HREC) of the Northern Territory Department of Health and Menzies School of Health Research (2019-3530), Far North Queensland HREC (2023/QCH/99606 (Nov ver 4)-1732), the Central Adelaide Local Health Network HREC (2023/HRE00209), the Aboriginal Health Council of South Australia (AHREC Protocol #: 04-23-1078), the Aboriginal Health and Medical Research Council of New South Wales (AH&MRC HREC reference: 2230/24) and the Far North Queensland Human Research Ethics Committee (FNQ HREC reference: HREC/2023/QCH/99606 (Nov ver 4)-1732). Study participants, policy makers and community organisations will be provided with updates of study findings. Dissemination of study findings will be through peer-reviewed publications and conference presentations.Trial registration number ACTRN12623001241628.